THE INFLUENCE OF THE READINGS WITH HISTORICAL CONTENT FROM THE PERIOD OF TURKISH-OTTOMAN RULE AND THE RECEPTION OF THE STUDENTS: (QUANTITATIVE AND QUALITATIVE ANALYSIS) (Journal of Contemporary Philology, 2021)
In this paper, I present the research results from the required readings in the curricula of Macedonian Language and Literature in high schools as well as their impact on the awareness of students about the “culture of Others” as members of the communities in the Republic of North Macedonia. The main goalof the research is, through literary analysis of textbooks, to develop empathy, understanding of others, of those different from themselves, to develop dialogue, communication, and interaction between students of different nationalities. The study, at the same time, is an analysis in which a critical attitude towards one’sown and other people’s culture and tradition is taken. There is a re-examination and personal transformation in order to recognize the identity representations, ethnic and religious stereotypes, and prejudices among ourselves and others, which would serve as a way to build mechanisms for their overcoming when implemented in schools. On the other hand, this study endeavors to identify thecommon, comprehensive, universal human values that contribute to overcoming differences with the goal of finding those universal human values in the literary works that are the subject of analysis. In this context, through the presentation and analysis of stereotypes and individual situations, efforts are made to point outthe possibilities for shaping the character of children and students in the spirit of the culture of interethnic tolerance.
Keywords: history; reading; pedagogy; stereotypes; prejudices